New Trends in Intercultural Communication Under New Conditions of Normalization in Sri Lanka - Sandunika Rathnayake (International Journal of Media and Communication Research (IJMCR), 2023)
The spread of the COVID-19 virus is a huge crisis that the whole world has had to face recently. Millions of lives were lost due to the spread of this virus, and Sri Lanka also had to face the impact of this. In this situation, almost every country in the world has introduced various health guidelines to protect people from the COVID-19 virus. The purpose of this research study was to identify the new trends in communication between each culture in Sri Lanka, specific to the COVID-19 guidelines, and communication during the period of the spread of the Covid virus. COVID-19 can be considered a health as well as a cultural crisis. Studying the behavior of the media in relation to this period, as well as how to inform people by exchanging information between each culture, was focused here. During the study, the data were collected by studying media reports, the use of literature, and the Internet. Accordingly, it was possible to determine how cultures worked more closely during the period when the new conditions of normalization were implemented, compared with the period in which people lived before. It was emphasized that the use of intercultural communication can be identified through measures taken by the government in such a way that it does not interfere with communication between people not only from one linguistic community, but also people with diversity in terms of religious, cultural, and social backgrounds. Thus, this study realized that cultural crises were overcome to a large extent with the help of intercultural communication, which was effectively carried out by the government of Sri Lanka for proper communication with the citizens of Sri Lanka, so-called multicultural state.